I-g+2(3+g)=-4(g+1)

Simple and best practice solution for I-g+2(3+g)=-4(g+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for I-g+2(3+g)=-4(g+1) equation:



-I+2(3+I)=-4(I+1)
We move all terms to the left:
-I+2(3+I)-(-4(I+1))=0
We add all the numbers together, and all the variables
-I+2(I+3)-(-4(I+1))=0
We add all the numbers together, and all the variables
-1I+2(I+3)-(-4(I+1))=0
We multiply parentheses
-1I+2I-(-4(I+1))+6=0
We calculate terms in parentheses: -(-4(I+1)), so:
-4(I+1)
We multiply parentheses
-4I-4
Back to the equation:
-(-4I-4)
We add all the numbers together, and all the variables
I-(-4I-4)+6=0
We get rid of parentheses
I+4I+4+6=0
We add all the numbers together, and all the variables
5I+10=0
We move all terms containing I to the left, all other terms to the right
5I=-10
I=-10/5
I=-2

See similar equations:

| 109=x-25 | | 5=2x10 | | -13-11q=16q+1+4q | | 6m-3=-15=2m | | xx8=72 | | 4m2 +6m+1=0 | | -13-11q=-16q+1 | | 5y+35=105 | | (3-x)(x+5)(x-1)=0 | | −7(−1+3a)=5(3−5a | | -13–11q=-16q+1+4q | | 2k^2=-27k-81 | | 3(2x+2)=4(x-5) | | -29=2(2a-1)+2a | | 100-60x=4 | | (x+3)(x-1)^2=0 | | x+2/7=6 | | 2z+10=4z | | -6y-7=9-8y | | 0.4x=4+x | | a/4+8=12 | | 3(j-1)=9 | | 30x+90=624.65 | | -(5x-9)=34 | | -219=1+5(-8-6x) | | 12x+8=-7+27 | | 6+4x-3x=-7-5 | | 2(2x-2)/3x=4 | | (5x-2)=58 | | 9x-9=4.5 | | -8*8+k=5 | | 9x-9=4,5 |

Equations solver categories